2007
DOI: 10.1029/2006wr005057
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization and preferential transport of soil particles during infiltration: A core‐scale modeling approach

Abstract: [1] Understanding particle movement in soils is a major concern for both geotechnics and soil physics with regard to environmental protection and water resources management. This paper describes a model for mobilization and preferential transport of soil particles through structured soils. The approach combines a kinematic-dispersive wave model for preferential water flow with a convective-dispersive equation subject to a source/sink term for particle transport and mobilization. Particle detachment from macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 38 publications
(78 reference statements)
1
22
0
Order By: Relevance
“…rain interruption duration (RID). Majdalani et al () studied the RID effect and found that the initial peak increased with RID up to about 200 h. They also found that the magnitude of the initial concentration peak was linked to the water content of the macropore, and that particles collected during the peak were >10 μm whereas most of the particles at the tail were <1 μm. They attributed the dependence of particle detachment on RID to differential capillary stresses which serve to regenerate a pool of detachable particles on pore walls between events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…rain interruption duration (RID). Majdalani et al () studied the RID effect and found that the initial peak increased with RID up to about 200 h. They also found that the magnitude of the initial concentration peak was linked to the water content of the macropore, and that particles collected during the peak were >10 μm whereas most of the particles at the tail were <1 μm. They attributed the dependence of particle detachment on RID to differential capillary stresses which serve to regenerate a pool of detachable particles on pore walls between events.…”
Section: Discussionmentioning
confidence: 99%
“…Majdalani et al () also applied the ADE to describe particle transport through macro‐porous soil and added a time dependent detachment rate, i.e. ‘detachment efficiency function’.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid infiltration during rainstorms also triggers water flow through macropores, which promotes the colloid transport in soils ( Poulsen et al, 2006; Vendelboe et al, 2011). A large fraction of transported colloids is released from the walls of the macropores ( Majdalani et al, 2007; Schelde et al, 2006), also pointing at the role of mechanical shear stress for the mobilization of colloids. An additional factor promoting the mobilization of colloids during rapid infiltration of water in macropores during heavy rainstorms is the rapid decrease of ionic strength ( Kretzschmar , 2005).…”
Section: Phosphorus Forms and Transport Fluxes In Soilsmentioning
confidence: 99%
“…Several authors have shown the influence of this factor on the retention of colloidal particles e.g. [9]- [14] [20]. Attachment due to ionic strength is partially reversible.…”
Section: Influence Of Potassium Bromide On the Retention Of Colloidalmentioning
confidence: 99%